Pemberdayaan Komunitas-Komunitas Perempuan di Desa Simpang Pematang Kabupaten Mesuji - Rizky Augia; Ahmad Gilang Satria; Muhammad Fharaz Ramadhan Anwar; Ratri Mawas Firdayanti; Umniyah Tsabitah Zahrani; Isaura Dewi fauzi; Serly Ulya Wardani (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
The empowerment of rural women is a strategic step toward inclusive and sustainable development. Women are not only responsible for household management but also serve as agents of change who contribute significantly to local economic development. In Simpang Pematang Village, the low participation of women in productive activities presents a challenge. This study aims to implement and evaluate empowerment programs that focus on stunting prevention education, post-harvest management workshops, and optimizing the use of home yards for economic and health benefits. The programs were conducted during the Community Service Program (KKN) from January 4 to February 10, 2024, through lectures, discussions, and evaluations. The results show increased awareness and participation of women in productive activities, contributing to improved family welfare and community development.